Kualitas Pelayanan Pegawai dalam Pembuatan E-KTP di Dinas Kependudukan dan Pencatatan Sipil Kutacane, Aceh Tenggara - Rifaldi, Rifaldi; Harahap, R. Hamdani; Hartono, Budi (Mahesa Research Center, 2022)
The purpose of this paper is to analyze the quality of E-KTP public services at the Southeast Aceh Regency Population and Civil Registration Service, and the two factors that hinder the E-KTP service at the Southeast Aceh Regency Population and Civil Registration Service. The method used in this study is descriptive with qualitative research instruments with observations, documentation studies and interviews. While the data analysis used descriptive analysis. The results showed that the quality of E-KTP public services which refers to Zeithaml's theory from the tangible dimension (physical evidence/infrastructure), realibility (reliability), responsiveness (responsiveness), assurance (guarantee), empathy (empathy) shows, the quality of public services E-KTP at the population and civil registration office of Southeast Aceh Regency has been running but is still not good or still not optimal. The inhibiting factors for E-KTP public services at Disdukcapil include inadequate human resources, limited financial resources, inadequate facilities and infrastructure, and lack of employee commitment. To improve the quality of public services, the E-KTP Disdukcapil must improve infrastructure, place employees in accordance with competence, increase employee discipline, and in service there should be no discrimination and prioritize service users/community.